Genealogi Riddah: dari Masalah Aqidah Menjadi Hudud - Imroatul Azizah (Proceedings of Annual Conference for Muslim Scholars, 2017)
The problem of riddah is initially only a theological problem, its responsibility only to God, so there was no world sanction. Historically, the Prophet never punished the apostate. But in a classical jurisprudence apostasy is categorisedas H}udu>dand punished with death penalty.Riddah became known after the rebellion of dissidents by Abu Bakr(h}uru>b al-riddah). This Abu Bakr’s decision and assertiveness be primary for the fuqaha to execute the perpetrators of the riddah. Ulama categorized Riddah be three Classification: First, Riddah engenders serious theological and sociological consequences. Riddah raises the concept of "kufr", and this is contrary to the main objective of Islamic law, preserving religion (li h}ifz} al-di>n). This doctrine is reinforced by sociological facts that riddah can weaken the unity of the people or at least could trigger the destruction of Islam; Secondly, in Islam there is no separation between religion and politics, disobedience to the state is synonymous with insubordination against Islam; and thirdly,the manner of Abu Bakr's government further becomes the discourse of thought and social action, entering into legal thought. This thinking further strengthened through the process of hegemony in various madhhab fiqh, disseminated through educational institutions and h}alaqah, so that the concept of riddah and legal sanction became accepted by the Muslim community as something taken for granted.But now contemporary scholars agree to conclude that 'illat of the penalty sanction of apostasy, not its kufr